On Virtual Economies - Edward Castronova (Center for Economic Studies and ifo Institute (CESifo), 2002)
Several million people currently have accounts in massively multi-player online games, places in cyberspace that are effectively large-scale shared virtual reality environments. The population of these virtual worlds has grown rapidly since their inception in 1996; significantly, each world also seems to grow its own economy, with production, assets, and trade with Earth economies. This paper explores two questions about these developments. First, will these economies grow in importance? Second, if they do grow, how will that affect real-world economies and governments? To shed light on the first question, the paper presents a brief history of these games along with a simple choice model of the demand for game time. The history suggests that the desire to live in a game world is deep-rooted and driven by game technology. The model reveals a certain puzzle about puzzles and games: in the demand for these kinds of interactive entertainment goods, people reveal that they are willing to pay money to be constrained. Still, the nature of games as a produced good suggests that technological advances, and heavy competition, will drive the future development of virtual worlds. If virtual worlds do become a large part of the daily life of humans, their development may have an impact on the macroeconomies of Earth. It will also raise certain constitutional issues, since it is not clear, today, exactly who has jurisdiction over these new economies.
Keywords: 330; information and internet services; computer software; synthetic worlds